2018
DOI: 10.3329/baj.v21i1.39363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inorganic and Organic Fertilizers on Growth and Yield of Soybean

Abstract: The experiment was executed at the Agronomy researchfield of Sher-e-Bangla Agricultural University, Dhaka-1207, during the period from November, 2015 to March, 2016 to study the effects of fertilizer management of different combinations of inorganic and organic fertilizers on growth, yield attributes and yield of soybean (var. BARI Soybean 6). The treatment combinations wereT0= Control, T1= fertilization at recommended fertilizer dose (RFD - urea 50 kg ha-1, TSP 150 kg ha-1, MoP 100 kgha-1, gypsum 80 kg ha-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 4 publications
(4 reference statements)
2
12
0
Order By: Relevance
“…The average of all harvests increased with DLM application, adjusting to a second degree polynomial function (Figure 1b), and the estimated dose for maximum yield was 126 m 3 ha -1 year -1 (9% increment). Other studies also found increased soybean yield by combining organic and mineral fertilizer [9,21,22]. Relative to winter crops, the wheat grain yield increased with DLM application in 2010 and 2014 harvests.…”
Section: Crops Yieldmentioning
confidence: 84%
See 1 more Smart Citation
“…The average of all harvests increased with DLM application, adjusting to a second degree polynomial function (Figure 1b), and the estimated dose for maximum yield was 126 m 3 ha -1 year -1 (9% increment). Other studies also found increased soybean yield by combining organic and mineral fertilizer [9,21,22]. Relative to winter crops, the wheat grain yield increased with DLM application in 2010 and 2014 harvests.…”
Section: Crops Yieldmentioning
confidence: 84%
“…It is known that improper use of manure can cause surface and groundwater pollution. Thus, the key to a proper manure management is to balance application rates with crop nutrient needs [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Zerihun and Haile (2017), the application of 3 t manure/ha can save 70-85% of input costs for the purchase of inorganic fertilizer. Mamia et al (2018) recommend the use of 10 t chicken manure/ha + 75% recommendation of inorganic fertilizer or 2 t vermicompost/ha + 75% recommendation of inorganic fertilizer compared to 100% of inorganic fertilizer to obtain soybean yield of 2 t/ha because it is more environmentally friendly. The general recommendation that can be delivered is to maintain the quality and productivity of soil and plants that are cultivated in a sustainable way, and then the input of organic and inorganic fertilizers is a viable alternative.…”
Section: Resultsmentioning
confidence: 99%
“…Neem organically formed fertilizer serves as a soil amendment and has been reported by Lokanadhan and Jeyaraman (2012) to increase soil nutrient contents such as nitrogen, phosphorus, sulphur, phosphorus, and calcium. Application of organic manure alone or in combination of chemical fertilizer will help to improve the physio-chemical properties of soils by providing a good substrate for the growth of microorganisms maintaining a favourable nutritional balance (Mamia et al, 2018).…”
Section: -47mentioning
confidence: 99%
“…Hartmann et al (2015) reported that the extensive application of synthetic fertilizers generates negative impacts on crop nutrient uptake, reduces soil quality, and causes environmental hazards. Proper fertilization is one of the major factors to gain higher yield but injudicious application of inorganic fertilizers without organic supplements causes environmental pollution, damaging soil physical, chemical and biological properties (Mamia et al, 2018). The incorporation of organic manure into the soil in order to augment soil structure and enhance adequate moisture for plant growth is a recommendable Garba, Y.,Yakubu, Z., Yakubu, A., Alhassan, J., Gana, M., Mohammed A.B.…”
Section: Introductionmentioning
confidence: 99%